Investigating the Effects of Sustainability Initiatives on Supply Chain Resilience and Performance in Indonesia - Basuki, Ahmad (International Journal of Supply Chain Management, 2024)
Abstract Purpose: The aim of the study was to investigating the effects of sustainability initiatives on supply chain resilience and performance Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The investigation into sustainability initiatives' effects on supply chain resilience and performance revealed significant benefits. Companies that integrated sustainable practices into their supply chain operations experienced improved resilience against disruptions, such as natural disasters or supply chain disruptions. Additionally, these initiatives often led to enhanced operational performance, including cost savings, efficiency improvements, and better relationships with stakeholders. Overall, the findings suggest that integrating sustainability into supply chain management can contribute positively to both resilience and performance outcomes. Unique Contribution to Theory, Practice and Policy: Resource-based view (RBV) theory, institutional theory & contingency theory may be used to anchor future studies on investigating the effects of sustainability initiatives on supply chain resilience and performance. Practitioners should prioritize the implementation of integrated sustainability strategies that align with organizational goals and supply chain objectives. Policymakers play a critical role in creating an enabling environment for sustainable supply chain management practices.